2023
DOI: 10.1128/spectrum.01627-23
|View full text |Cite
|
Sign up to set email alerts
|

The Heat Shock Transcription Factor HsfA Plays a Role in Membrane Lipids Biosynthesis Connecting Thermotolerance and Unsaturated Fatty Acid Metabolism in Aspergillus fumigatus

Abstract: Aspergillus fumigatus causes invasive pulmonary aspergillosis, a life-threatening infection accounting for high mortality rates in immunocompromised patients. The ability of this organism to grow at elevated temperatures is long recognized as an essential attribute for this mold to cause disease. A. fumigatus responds to heat stress by activating heat shock transcription factors and chaperones to orchestrate cellular responses that protect the fungus against damage caused by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 94 publications
0
0
0
Order By: Relevance
“…An interesting result from our MBX-7591 spectrum of activity screen is the lack of activity against other tested Aspergillus species. It seems clear that A. fumigatus possesses one functional copy of SdeA, as detailed by Fabri et al ( 42 ) and confirmed here, which is in contrast with other Aspergillus species (Table S9). Thus, one possibility to explain the MBX-7591 resistance in other Aspergillus species, if SdeA is the molecular target, is an increase in functional sdeA copy number.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…An interesting result from our MBX-7591 spectrum of activity screen is the lack of activity against other tested Aspergillus species. It seems clear that A. fumigatus possesses one functional copy of SdeA, as detailed by Fabri et al ( 42 ) and confirmed here, which is in contrast with other Aspergillus species (Table S9). Thus, one possibility to explain the MBX-7591 resistance in other Aspergillus species, if SdeA is the molecular target, is an increase in functional sdeA copy number.…”
Section: Discussionsupporting
confidence: 85%
“…S4). Strikingly, our lipid profile of MBX-7591-treated A. fumigatus cells is highly similar to the lipid profile of the conditional sdeA strain characterized by Fabri et al ( 42 ) highlighted by the increase in saturated phospholipids and decrease in monounsaturated fatty acids. Similar to oleic acid complementation of the sdeA genetic mutant strains, MBX-7591 antifungal activity is significantly reduced in the presence of oleic acid.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations